Unraveling spinal cord injury caregiver burden in Indonesia - Biben, Vitriana; Sumardi, Novitri; Wijaya, Arya; Simatupang, Septania Elfira; Nurarifah, Sitti Ayu Hemas (Intelektual Pustaka Media Utama, 2024)
Diverse cultural, social, and economic backgrounds significantly influence the caregiver burden of spinal cord injury (SCI) patients, affecting their quality of life (QoL) and the overall care experience. This study was done to identify spinal cord caregivers' QoL in Indonesia through their burden and the variables that influence it. A cross-sectional study was conducted at Dr. Hasan Sadikin Hospital, Bandung, Indonesia, involved 137 primary SCI caregivers. The burden of these caregivers was evaluated using the Indonesian version of the Zarit Burden Interview (ZBI) and the World Health Organization Quality of Life-BREF questionnaires. The data was analyzed with multiple linear regression and spearman analysis using SPSS version 24. The majority of SCI caregivers have a mild to moderate burden (54.7%). The burden score was significantly correlated, especially with occupational status and the length of interaction each day (p<0.001). It also found a significant with strong negative correlation (referring to the Guilford criteria) between caregiver burden and QoL (r-value −0.750; p-value <0.001). Indonesian caregivers' cultural and economic backgrounds may alleviate their burden in caregiving, but attention to patient occupational status and care duration is crucial to prevent worsening their quality of life, particularly for SCI survivors they care for.